"Combination of Thoracic Epidural Anesthesia, Supraclavicular Brachial Plexus Block and Supraclavicular Nerve Block as Surgical Anesthesia for Modified Radical Mastectomy—A Case Series". Issue 6 (7th June 2022) - Surya, R.; Joseph Gunasingh, Jennifer Lydia; Sethuraman, Raghuraman M.; Asokan, Aswin; Thilak, M.
Abstract : Sensory innervation of the breast is complex, thereby making it difficult to perform any surgical procedure with a single regional anesthesia technique. Because of the involvement of pectoral muscles and extension of the incision into the axilla, a modified radical mastectomy makes it further challenging and requires multiple techniques. We have used a new combination of regional techniques in this case series and found that it provided complete surgical anesthesia with a smaller volume of local anesthetic.